De volmaakte Wagneriaan: De Ring des Nibelungen toegelicht - Shaw, Bernard 1856-1950; Stapper, Léon (Amsterdam Wereldbibliotheek, 1998)
In 1885, 29-year-old Bernard Shaw was rescued by a friend from daily poverty and experienced rejection slips from numerous publishers: he got him a paid job as a journalist. In a short time, Shaw became a celebrated and feared author and critic: in addition to his own plays, he wrote about literature, painting, drama and music. The Perfect Wagnerian, his essay on the 'Ring des Nibelungen', was published in 1898, at the height of his fame as a polemicist and critic.‘I am not one of “Art for art's sake”,’ Shaw once remarked to Tolstoy. ‘I wouldn't make any effort to create a work of art if I knew there wouldn't be more in it.’ In The Perfect Wagnerite, Shaw sets out his vision of Wagner's music and the ideas behind it, and inimitably shows how much more there is in a work of art like the 'Ring des Nibelungen'. Shaw's fabulous knowledge of music, theatre and politics guarantees an explanation that highlights the dramatic and musical aspects, but also addresses the socially critical side of the 'Ring'. (Translated with DeepL.com)
Keywords: Wagner, Richard -- 1813-1883; 19th Century (1801-1900); Music history; Musical analysis; Opera; Mythology